An Exploration into Teachers’ Perceptions towards the challenges of Teaching Reading Skills using Communicative Language Teaching Approach: Focus on Wolaita Sodo Preparatory School - Tesfaye Buche Bosha; Desalegn Youpo Ukute (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
The main purpose of this study is to explore teachers’ perceptions towards the challenges of teaching reading skill using communicative language teaching approach: focus on Wolaita Sodo Preparatory School. Descriptive research design was employed. The data were collected through semi-structured interview and classroom observations. Six grade eleven EFL (English as a Foreign Language) teachers of the Wolaita Sodo Preparatory school were selected as of the study using convenience sampling method. The Interview data were tape recorded and transcribed into textual form and the classroom observation data were noted to analyze. The findings of this study disclosed that EFL teachers have a positive perception in towards teaching/reading skills using communicative language teaching approach but students were negatively perceived in learning/reading using Communicative Language Teaching (CLT). Hence, based on the findings, recommendations were made. In concurrence to this, the researcher recommends that the concerned bodies should give due attention to overcome selected problems which hampers teaching/reading skills using communicative language teaching approach particularly mobilizing EFL teachers through continuous capacity building activity is paramount.